The historical development for use of force - Ali Omar Moftah Medon,; Ahmad Muhammad Husni, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study tackles the historical development for force use since the ancient time, to the time it was taken into account and organized in the Charter of the United Nations. The research problem was repsented by the over-use of power from the ancient times until our time. The historical approach was adopted; that is by referring to the past we can understand the present. The objective of this paper is to state the phases the orgnization of this power passed through, and how countries used to deal with those who use power. The result reached at is that the ancient societies with whatever civilizational development they had used to resort to the means of violence and power for simple reasons, and that the most significant reasons for originating that conflict and clash were the absence of communication between these societies and the difference of the cultural and intellectual development among them, and also the pursuit of trade and water resources and other resources which legalize possessing all properties the other used to have.